Nitrogen-Doped Magnetic-Dielectric-Carbon Aerogel for High-Efficiency Electromagnetic Wave Absorption - Wang, Shijie; Zhang, Xue; Hao, Shuyan; Qiao, Jing; Wang, Zhou; Wu, Lili; Liu, Jiurong; Wang, Fenglong (Nano-Micro Letters, 2023)
Carbon-based aerogels derived from biomass chitosan are encountering a flourishing moment in electromagnetic protection on account of lightweight, controllable fabrication and versatility. Nevertheless, developing a facile construction method of component design with carbon-based aerogels for high-efficiency electromagnetic wave absorption (EWA) materials with a broad effective absorption bandwidth (EAB) and strong absorption yet hits some snags. Herein, the nitrogen-doped magnetic-dielectric-carbon aerogel was obtained via ice template method followed by carbonization treatment, homogeneous and abundant nickel (Ni) and manganese oxide (MnO) particles in situ grew on the carbon aerogels. Thanks to the optimization of impedance matching of dielectric/magnetic components to carbon aerogels, the nitrogen-doped magnetic-dielectric-carbon aerogel (Ni/MnO-CA) suggests a praiseworthy EWA performance, with an ultra-wide EAB of 7.36 GHz and a minimum reflection loss (RLmin) of − 64.09 dB, while achieving a specific reflection loss of − 253.32 dB mm−1. Furthermore, the aerogel reveals excellent radar stealth, infrared stealth, and thermal management capabilities. Hence, the high-performance, easy fabricated and multifunctional nickel/manganese oxide/carbon aerogels have broad application aspects for electromagnetic protection, electronic devices and aerospace. Highlights: 1 An ingenious design achieved magnetic-dielectric-carbon coupling. 2 Nickel and manganese oxide particles were in situ reduced and grew on the carbon aerogels. 3 The aerogels demonstrated radar stealth, infrared stealth and thermal management capability.